In-depth comparative proteomic analysis of yeast proteome using iTRAQ and SWATH based MS1. Issue 8 (14th August 2015) - Basak, Trayambak; Bhat, Ajay; Malakar, Dipankar; Pillai, Manoj; Sengupta, Shantanu
<x xml:space="preserve">Abstract</x> SWATH is capable of quantifying proteins of lower abundance as compared to iTRAQ.